IMPLEMENTASI METODE PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS DI SMAK SANTO PETRUS ENDE - Separ, Fransiskus Maria (LPPM Institut Pendidikan Nusantara Global, 2023)
Learning using the Role Playing learning method aims to improve the English learning outcomes of Class The research method used is classroom action research (PTK). Data collection techniques in this research used test techniques and observation techniques. Data analysis in this research uses test data analysis techniques and observation data analysis techniques. The research results show that there is an increase in English learning outcomes through the Role Playing learning method. This is indicated by the average learning outcomes and classical completeness of students in the first cycle of 61.89 with classical completeness of 17.24%; cycle II was 76.20 with classical completeness of 68.96%; and in cycle III it was 80.17 with classical completeness of 89.65%. Apart from learning outcomes, student activity also increased, where in cycle I the average activity of students who were actively involved was 24.13%, students who were passively involved was 34.48%, and students who were not involved was 41.37%. In cycle II the average activity of students who were actively involved was 65.51%, students who were passively involved was 27.58%, and students who were not involved were 6.89%. And in cycle III the average activity of students who were actively involved was 89.65%, students who were passively involved was 6.89%, and students who were not involved were 3.44%.